Significant solutions in minimising construction defects occurrence during Defect Liability Period (DLP) for residential projects in Kuala Terengganu/ Najihah Rahimin ... [et al.] - Rahimin, Najihah; Mohd Isa, Haryati; Mohd, Thuraiya; Ahmad, Nur Azfahani (Universiti Teknologi MARA, Perak, 2024)
Construction defects are a widespread problem in Malaysia, just as they are in other countries throughout the world. Furthermore, a significant proportion of the construction defects that have arisen are not adequately documented. Particular defects have the potential to bring about the emergence of further problems. It is possible to prevent the creation of several additional problems if the basic defects are identified and resolved at an early point in the process. The primary objective of this research was to recommend significant solutions toward minimising construction defect occurrence during the defect liability period for residential projects in Kuala Terengganu. To gather insights, a questionnaire survey targeting 71 registered building surveyors was conducted and 30 positive responses were returned in a usable format with a 42% response rate. The survey instrument gauged their perspectives on mitigating construction defects. Correspondingly, 30 questionnaires were collected and analysed using descriptive analysis and Confirmatory Factor Analysis (CFA) using SPSS software version 29 to derive findings. The results emphasize the importance of implementing a six-phase approach to efficiently minimize construction defects. These phases include raising awareness, conducting investigations, identifying defects, evaluating findings, implementing remedies, and pursuing financial recovery. Such a systematic approach holds promise for offering substantial solutions to mitigate construction defects in residential projects, serving as valuable references for stakeholders including the construction industry, developers, and the public. Moreover, this study fills a notable gap in the existing literature and enhances understanding of construction defects, paving the way for the adoption of improved construction methodologies in the future.